USE OF NON DIRECTIVE METHOD IMPROVE STUDENT LEARNING ACTIVITIES AND RESULT IN CLASS VII SMPN I CILENGSI BOGOR - Lengsi Manurung (Peneliti.net, 2019)
The objectives of this study are: (1) Class VII-1 student learning activities at SMP Negeri 1 Cilengsi Bogor in the application of the Non-Directive Method by using media maps. (2) learning outcomes of students of class VII-1 IPS in the application of the Non-Directive Method by using media maps. The subjects in this research were 38 students of Class VII-1 Middle School 1 Cilengsi Bogor. data collection techniques using direct and indirect communication. Data collection tools in this study used observation sheets and tests. The test is used in accordance with the curriculum objectives achieved and taken from social studies textbooks VII-1 class SMP Negeri 1 Cilengsi Bogor. to collect research data using LKS and test post. This research was conducted with 2 cycles, namely cycle I and cycle II. each cycle has stages, namely planning, implementing, observing and reflecting. the results of this study indicate that an increase in students' learning abilities with student completeness reached 35.18% then increased in the second cycle to 46.22%. from the results of the study can also be seen an increase in students' learning abilities with worksheets in the second cycle to 94.44%. From the analysis conducted, it can be concluded that the Non Directive learning method can increase the Activities and Student Learning Outcomes of students of SMP Negeri 1 Cilengsi Bogor in Academic Year 2010/2011.